The study of gap acceptance at roundabouts / Norhasyimah Shafie - Shafie, Norhasyimah (2007)
This research is to study the gap acceptance at roundabouts and data collection using video recording. The scope of the research is only unsignalized conventional roundabout and gap acceptance on each vehicle. Two (2) unsignalized roundabouts at Bulatan Bestari, Seksyen 2 and Bulatan Kayangan, Seksyen 13 which are located in Shah Alam are involved in order to achieve the research objectives. Then the data was analysed on time gap as a parameter. The extracted data from video recording had been analysed and summarized into table and graph chart in Microsoft Excel. The result showed the highest time for accepted gap and the comparison number of vehicle involved in gap acceptance between off-peak and peak hour at the locations. The gap acceptance should be studied for more detail in order to understand its concept especially to evaluate delay, waiting times and queue lengths. Hence, this study can be used to improve a road condition, road geometric design, vehicles capacity and traffic safety for users.